Anti-vibration seat of transport vehicle operator - P. D. Balakin; O. S. Dyundik; I. P. Zgonnik; A. V. Krivtsov (Омский научный вестник)
Vibration isolation of personnel and machine units is an urgent problem that requires a comprehensive approach to its resolution. The article presents effective technical solutions of the vibration isolation system, characterized by structural simplicity and having in its composition other elements with a linear stiffness characteristic, but with a special location to the vibration displacements of the protected object. It is shown that in the systems «jump» in a certain range of achievable effect quasizero stiffness of the support given by the simplest, tech, universal technical solution of the anti-vibration seat of a transport vehicle.